THE EFFECT OF MIXED CROPPING OF Brachiaria decumbens WITH THREE DIFFERENT TYPES OF LEGUMES IN ULTISOL SOILS ON CP, CFib, Ca AND P CONTENT OF GRASS - Arini Nur Fitriansa; Dina Syafira Putri; Herryawan Kemal Mustafa; Nyimas Popi Indriani (Unpad Press, 2022)
Research on mixed cultivation of Brachiaria decumbens grass with three different types of legumes on ultisol soils on the PK, SK, Ca, and P content of grass was carried out from April to July 2022 at the Experimental Garden of Animal Food Crops Laboratory, Faculty of Animal Husbandry, Padjadjaran University. The purpose of this study was to determine the effect of mixed cultivation of Brachiaria decumbens grass with three different types of legumes on ultisol soils on the PK, SK, Ca, and P content of grass. The study was conducted for 3 months with an experimental method using a randomized block design (RAK) with 4 treatments and 6 replications. This experiment consisted of P0 = Brachiaria decumbens grass, P1 = Brachiaria decumbens grass + Arachis pintoi grass, P2 = Brachiaria decumbens grass + Canavalia gladiata legume, P3 = Brachiaria decumbens grass + Centrosema pubescens legume. The results showed that the mixed cropping treatment of Brachiaria decumbens grass with three types of legumes significantly affected the PK, SK, and P content of the grass, but did not significantly differ on the Ca content of the grass. Mixed cultivation of Brachiaria decumbens grass with sword koro beans (Canavalia gladiata) resulted in the highest average crude protein content and the lowest crude fiber, namely 12% and 23.32%, respectively. Planting a mixture of Brachiaria decumbens grass with Arachis pintoi produced the highest average phosphorus content of 0.57%.